Family Limitation - Sanger, Margaret, 1879-1966 (London : Bakunin Press, 1920)
1920 1920 1920s 16 pages : illustrations 16 FAMILY LIMITATION I have given in the foregoing pages the most commonly known means of prevention. Personally I recommend every poor woman who has had at least one child to use a well fitted Mizpah pessary and learn to adjust it. Birth control, or family limitation, has been recommended by some of the leading physicians of the United States and Europe. The movement can no longer be set back by setting up the false cry of "Obscenity." It has already been incorporated into the private moral code of millions of the most influential families in every civilized country. It will shortly win full acceptation and sanction by public morality as well. In cases of women suffering from serious ailments, such as Bright's disease, heart disease, insanities, melancholia, idiocy, consumption, and syphilis, all a physician is allowed to do is to tide these women through their pregnancies if possible. Even though the life of the woman is positively endangered, he cannot relieve her without calling a colleague in consultation. Therefore, the mortality of mothers suffering from these diseases, and their infants, is very high, and premature births common. To conserve the lives of these mothers and to prevent the birth of diseased or defective children are factors emphasizing the crying need of a sound and sane educational campaign for birth control. BY THE SAME AUTHOR. WHAT EVERY GIRL SHOULD KNOW. Teaches girls to understand themselves, their anatomy, including sex anatomy; the epochs of a normal woman's life, and the unfoldment which each epoch brings ; the effect the emotions have on actions, and the fulness and richness of life when crowned by the flower of motherhood. This book will dispel ignorance of the sex functions, and thus contribute to healthy and clean living. "WHAT EVERY MOTHER SHOULD KNOW." Price, 2s. 6d. each. Post Free. "THE BIRTH CONTROL REVIEW." One Dollar 50 cents. a year. Address: 104 Fifth Ave., New York City. All obtainable through the Bakunin Press. 15X/2/490/4